2019
DOI: 10.1016/j.watres.2019.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Comammox Nitrospira are the dominant ammonia oxidizers in a mainstream low dissolved oxygen nitrification reactor

Abstract: Recent findings show that a subset of bacteria affiliated with Nitrospira, a genus known for its importance in nitrite oxidation for biological nutrient removal applications, are capable of complete ammonia oxidation (comammox) to nitrate. Early reports suggested that they were absent or present in low abundance in most activated sludge processes, and thus likely functionally irrelevant. Here we show the accumulation of comammox Nitrospira in a nitrifying sequencing batch reactor operated at low dissolved oxyg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
154
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(167 citation statements)
references
References 37 publications
10
154
1
2
Order By: Relevance
“…We know now that a single population can oxidize ammonia all the way to nitrate. These are the ‘Comammox’ Nitrospira related bacteria, and occur widely, including in N removal wastewater treatment plants (Daims et al, 2015; Roots et al, 2019). Equally unexpectedly, Sorokin et al (2014) isolated successfully a non-filamentous Chloroflexi nitrifying bacterium, Nitrolancea hollandica , which this review shows occurs in activated sludge systems (see later).…”
Section: Nutrient Removal Plantsmentioning
confidence: 99%
“…We know now that a single population can oxidize ammonia all the way to nitrate. These are the ‘Comammox’ Nitrospira related bacteria, and occur widely, including in N removal wastewater treatment plants (Daims et al, 2015; Roots et al, 2019). Equally unexpectedly, Sorokin et al (2014) isolated successfully a non-filamentous Chloroflexi nitrifying bacterium, Nitrolancea hollandica , which this review shows occurs in activated sludge systems (see later).…”
Section: Nutrient Removal Plantsmentioning
confidence: 99%
“…Our results provide the first in situ physiological evidence of ecologically relevant NH 4 + oxidation by comammox Nitrospira in any environment. Other reports of in situ activity are inferred from bulk observations (ammonium removal when comammox Nitrospira bacteria are more abundant than AOB or AOA [20, 41]) or from comammox-specific amoA transcript analysis (42). Our former observations that Nitrospira was more abundant than Nitrosomonas and the discovery that Nitrospira harbors the complete nitrification pathway in a full-scale RGSF microbiome (8, 10, 11) are thus directly linked to the ammonia-oxidizing activity of Nitrospira in this environment.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of sublineage I Nitrospira progressively decreased with increasing DO levels [63]. Roots et al [64] reported that comammox Nitrospira is an efficient nitrifier in WWTPs at low DO levels. The most common nitrifying bacteria such as Nitrosomonas and Nitrobacter are least abundant or absent in freshwater biofilters [60].…”
Section: Ecophysiologymentioning
confidence: 99%